Comparative ex vivo infection with Trypanosoma cruzi and Toxoplasma gondii of human, canine and ovine placenta: Analysis of tissue damage and infection efficiency. (June 2020) - Liempi, Ana; Castillo, Christian; Medina, Lisvaneth; Galanti, Norbel; Maya, Juan Diego; Parraguez, Victor Hugo; Kemmerling, Ulrike
Abstract: Trypanosoma cruzi, the causative agent of Chagas disease, and Toxoplasma gondii, which is responsible for Toxoplasmosis, are two parasites that cause significant protozoan zoonoses and consequently important economic losses in human, companion animals and livestock. For the congenital transmission to occur, both parasites must cross the barrier present in the mammalian placenta, which differs between species. Particularly, hemochorial, endotheliochorial and epitheliochorial placental barriers are present, respectively, in human, dog and sheep. The type of placental barrier has been associated with the probability of transmission of pathogens. In this study, we used experimental placental ex vivo infection models of T. cruzi and T. gondii in the above-mentioned mammals in order to study tissue alterations and to compare infection efficiency. Here, we infected placental term explants from human, dog and sheep and analyzed tissue damage by standard histological and histochemical methods. Comparative infection efficiency was determined by quantitative PCR. Both parasites are able to infect the different placental explants; however, more T. gondii parasites were detected, and T. gondii causes a more severe tissue damage in human and canine explants than T. cruzi . The histopathological changes observed in ovine placenta explants were similar in presence of both parasites. We conclude that the infection efficiency of T. gondii is higher, compared to T. cruzi, during the ex vivo infection of human, canine and ovine placental explants. In addition, the ex vivo infection of mammalian placental explants constitutes an interesting experimental approach to study part of the infection mechanisms as well as host responses during congenital infection of both parasites. Graphical abstract: Unlabelled Image Highlights: T. cruzi infects human, canine and ovine placental explants. T. gondii infects human, canine and ovine placental explants. T. gondii present a higher infection efficiency than T. cruzi. Both parasites induce a severe tissue damage in placental explants.